2019
DOI: 10.1113/ep088058
|View full text |Cite
|
Sign up to set email alerts
|

Influence of methazolamide on the human control of breathing: A comparison to acetazolamide

Abstract: Acetazolamide is used to prevent/treat acute mountain sickness and both central and obstructive sleep apnoea. Methazolamide, like acetazolamide, reduces hypoxic pulmonary vasoconstriction, but has fewer side-effects, including less impairment of skeletal muscle function. Given that the effects of methazolamide on respiratory control in humans are unknown, we compared the effects of oral methazolamide and acetazolamide on ventilatory control and determined the ventilationlog P O 2 relationship in humans. In a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…3B). A logarithmic function has been previously shown to be useful when comparing groups with different ODCs (33,35). The ventilatory response was also not different when expressed in absolute units; however, the response was nonlinear as expected (Fig.…”
Section: Discussionsupporting
confidence: 64%
“…3B). A logarithmic function has been previously shown to be useful when comparing groups with different ODCs (33,35). The ventilatory response was also not different when expressed in absolute units; however, the response was nonlinear as expected (Fig.…”
Section: Discussionsupporting
confidence: 64%
“…Its negative effect on the diaphragm and skeletal muscles, which occurs when using acetazolamide, has not been noticed. [26] Inhaled budesonide turns out to be ineffective in preventing severe altitude sickness, but it helps reduce blood pressure and increase blood saturation. It may be effective in preventing mild disease.…”
Section: Pharmacological Treatment and Preventionmentioning
confidence: 99%
“…It is known to be more soluble in lipids than acetazolamide and thus can cross cellular membranes more easily (Maren, 1967). As with acetazolamide, it induces metabolic acidosis by causing renal bicarbonate excretion to effectively increase circulating [H + ], stimulate ventilation and improve arterial oxygenation in hypoxia (Teppema et al., 2020). It has been used for AMS prophylaxis since the 1980s, and in a limited number of studies has been shown to reduce symptoms (Forster, 1982), with at least one study reporting fewer side effects than acetazolamide (Wright et al., 1983).…”
Section: Introductionmentioning
confidence: 99%
“…xia (Teppema et al, 2020). It has been used for AMS prophylaxis since the 1980s, and in a limited number of studies has been shown to reduce symptoms (Forster, 1982), with at least one study reporting fewer side effects than acetazolamide (Wright et al, 1983).…”
mentioning
confidence: 99%